2015
DOI: 10.1364/prj.3.000094
|View full text |Cite
|
Sign up to set email alerts
|

Dual-wavelength rectangular pulse erbium-doped fiber laser based on topological insulator saturable absorber

Abstract: We reported on the generation of the dual-wavelength rectangular pulse in an erbium-doped fiber laser (EDFL) with a topological insulator saturable absorber. The rectangular pulse could be stably initiated with pulse width from 13.62 to 25.16 ns and fundamental repetition rate of 3.54 MHz by properly adjusting the pump power and the polarization state. In addition, we verified that the pulse shape of the dual-wavelength rectangular pulse can be affected by the total net cavity dispersion in the fiber laser. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…A 5 m highly nonlinear fiber (HNLF) is used to enhance the nonlinearity of the cavity, which has a nonlinear coefficient γ 10 W −1 • km −1 with dispersion of 0 1 ps∕nm∕km. The high nonlinearity plays an important role in broadening the tuning range of the pulse width [3,12] and multipulse operation [4,13]. The pigtails of other optical components are 11.5 m standard SMFs with a dispersion of 17 ps/nm/km.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 5 m highly nonlinear fiber (HNLF) is used to enhance the nonlinearity of the cavity, which has a nonlinear coefficient γ 10 W −1 • km −1 with dispersion of 0 1 ps∕nm∕km. The high nonlinearity plays an important role in broadening the tuning range of the pulse width [3,12] and multipulse operation [4,13]. The pigtails of other optical components are 11.5 m standard SMFs with a dispersion of 17 ps/nm/km.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, DSR is an effective way to scale singlepulse energy in fiber lasers. Followed by numerous successive publications, researchers investigated DSR mode-locking in a variety of laser configurations under both anomalous and normal dispersion regimes [2][3][4][5][6]. Both theoretical and experimental investigations suggested that the dispersion plays an important role in DSR pulse generation.…”
Section: Introductionmentioning
confidence: 99%
“…126 In many cases, bismuth chalcogenides are used in the form of powders 127 or microfibers, 125,128-132 which do not exhibit TSS. Therefore, the efficiency of antimony or bismuth chalcogenides as saturable absorbers 125,128,131,[133][134][135][136][137][138][139][140] has nothing related to topological phases of matter, in spite of the wealth of claims in the literature. Nevertheless, in the following we briefly discuss the most important findings of this research topic.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…With increasing pump power, the DSR pulse keeps broadening its pulse width with a clamped peak power without suffering pulse breaking, which shows great potential for high-energy pulse generation in fiber lasers. During the past decade, the DSR phenomenon has been extensively investigated theoretically and experimentally with different dispersion regimes, mode-locking techniques and emission wavelengths [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. It was found that the peak-power-clamping effect caused by reverse saturable absorption plays an important role in the formation of DSR pulses.…”
Section: Introductionmentioning
confidence: 99%